2014
DOI: 10.1155/2014/521349
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiological Pathogenesis of Poststroke Depression

Abstract: Poststroke depression (PSD) is an important consequence after stroke, with negative impact on stroke outcome. The pathogenesis of PSD is complicated, with some special neurobiological mechanism, which mainly involves neuroanatomical, neuron, and biochemical factors and neurogenesis which interact in complex ways. Abundant studies suggested that large lesions in critical areas such as left frontal lobe and basal ganglia or accumulation of silent cerebral lesions might interrupt the pathways of monoamines or rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 96 publications
2
61
1
2
Order By: Relevance
“…[1] Patients with PSD usually present with a wide range of symptoms, including apathy, weight changes, sleep disturbances, feelings of worthlessness, and fatigue. [2] It is already well documented that PSD impedes rehabilitation and reduces the quality of life in majority of stroke survivors. [3] However, up to now, the pathophysiological mechanisms of PSD are still not fully illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Patients with PSD usually present with a wide range of symptoms, including apathy, weight changes, sleep disturbances, feelings of worthlessness, and fatigue. [2] It is already well documented that PSD impedes rehabilitation and reduces the quality of life in majority of stroke survivors. [3] However, up to now, the pathophysiological mechanisms of PSD are still not fully illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that alterations in neurotransmission during and after stroke may contribute to the development of depression (Whyte and Mulsant 2002). To support this hypothesis, studies using animal models of PSD have shown that several brain regions including the hippocampus, frontal cortex, and hypothalamus are critically involved in the development of PSD (Wang et al , 2010bFeng et al 2014;Shao et al 2015). Furthermore, various signaling molecules and neurotransmitters as well as their receptors have been shown to be involved in the development of PSD (Wang et al , 2010bFeng et al 2014;Shao et al 2015).…”
mentioning
confidence: 98%
“…To support this hypothesis, studies using animal models of PSD have shown that several brain regions including the hippocampus, frontal cortex, and hypothalamus are critically involved in the development of PSD (Wang et al , 2010bFeng et al 2014;Shao et al 2015). Furthermore, various signaling molecules and neurotransmitters as well as their receptors have been shown to be involved in the development of PSD (Wang et al , 2010bFeng et al 2014;Shao et al 2015). However, few studies have been conducted to investigate the role of cannabinoid receptors in the development of PSD, even though increasing evidence suggests that cannabinoid receptor subtype 1 (i.e., CB1 receptor) is one of the critical substrates underlying the pathogenesis of depression (Aso et al 2011).…”
mentioning
confidence: 99%
“…Large infarction may result in severe damage to the critical areas associated with modulating emotional behaviour and biochemical change . According to this hypothesis, cerebral lesions interrupt the projections ascending from the midbrain and brainstem, passing through the thalamus and basal ganglion, and reaching the frontal cortex; this then results in a decrease in the bioavailability of biogenic amines, including serotonin, dopamine, and noradrenaline, and thus in depressive symptoms .…”
Section: Discussionmentioning
confidence: 99%